Relationship Assessment Between Adverse Childhood Experiences (Aces) With Psychological Well-Being (PWB) - Bibi, Khansa; Rumi, Jalaluddin; Zahir, Sardar Muhammad; Lehri, Shabir Ahmed; Iqbal, Muhammad; Ullah, Naseeb; Ullah, Amin; Kakar, Sana Ullah (Biological and Clinical Sciences Research Journal, 2025)
Adverse Childhood Experiences (ACEs) have been recognized as potent predictors of psychological functioning in adulthood. These early life stressors, encompassing abuse, neglect, and household dysfunction, can significantly impair psychological well-being (PWB). Despite growing global evidence, the intersection of ACEs with age and gender as moderating factors in psychological outcomes remains underexplored in the Pakistani context, particularly among university students. Objective: To examine the relationship between adverse childhood experiences (ACEs) and psychological well-being (PWB) among university students in Quetta, Pakistan, and to investigate the moderating effects of age and gender on this relationship. Methods: A cross-sectional study was conducted among 145 university students, stratified into two age groups (18–24 and 25–30 years), across Quetta, Pakistan. Data were collected using the conventional 10-item Adverse Childhood Experiences (ACEs) questionnaire and a shortened 18-item version of the Psychological Well-Being (PWB) scale covering six domains (autonomy, environmental mastery, personal growth, positive relations, purpose in life, and self-acceptance). Statistical analysis included independent samples t-tests to assess mean differences by age and gender, and correlation analysis to examine the relationship between ACEs and PWB. Results: The results showed a statistically significant relationship between ACEs and PWB (p < 0.05). A mean difference was observed between the two age groups on the ACEs scale (p = 0.04), but the mean difference on the PWB scale was not significant (p = 0.388). Gender-based analysis indicated no statistically significant mean differences on the ACEs (p = 0.782) or PWB (p = 0.841) scales. However, correlation analysis affirmed a negative association between higher ACE exposure and lower psychological well-being. Conclusion: The findings suggest a significant inverse relationship between adverse childhood experiences and psychological well-being among university students. Although age showed a significant impact on ACE scores, gender did not appear to influence either ACEs or PWB significantly. These results underscore the importance of early trauma-informed interventions in improving psychological health outcomes in youth populations.